2009
DOI: 10.1007/s00401-009-0619-8
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes: biology and pathology

Abstract: Astrocytes are specialized glial cells that outnumber neurons by over fivefold. They contiguously tile the entire central nervous system (CNS) and exert many essential complex functions in the healthy CNS. Astrocytes respond to all forms of CNS insults through a process referred to as reactive astrogliosis, which has become a pathological hallmark of CNS structural lesions. Substantial progress has been made recently in determining functions and mechanisms of reactive astrogliosis and in identifying roles of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

77
3,951
9
61

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 4,248 publications
(4,098 citation statements)
references
References 259 publications
(391 reference statements)
77
3,951
9
61
Order By: Relevance
“…Consistent with previous studies, herein, our data demonstrate that long‐term metformin pretreatment affords strong neuroprotection and can be lifesaving under the conditions of CA/CPR. Moreover, our data show that metformin pretreatment suppresses the activation of microglia and astrocytes, which may represent part of the mechanism accounting for metformin‐mediated neuroprotection in CA/CPR because microgliosis and astrocytosis are well known to contribute to delayed neuronal loss and mitochondria dysfunction in ischemic brain injuries 41, 42, 43…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with previous studies, herein, our data demonstrate that long‐term metformin pretreatment affords strong neuroprotection and can be lifesaving under the conditions of CA/CPR. Moreover, our data show that metformin pretreatment suppresses the activation of microglia and astrocytes, which may represent part of the mechanism accounting for metformin‐mediated neuroprotection in CA/CPR because microgliosis and astrocytosis are well known to contribute to delayed neuronal loss and mitochondria dysfunction in ischemic brain injuries 41, 42, 43…”
Section: Discussionmentioning
confidence: 74%
“…Our results also showed that BMP4 strongly suppressed maturation of primary OPCs and converted OPCs into astrocytes in differentiation media. Compared with 1.2‐ to 2‐fold changes in angiogenesis, the degree of inducing astrogliogenesis 49 and suppressing oligodendrogenesis was exponential. Furthermore, even when the OPCs were cultured in proliferation media which should maintain an OPC state, BMP4 treatment decreased Pdgfra mRNA expression in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…SERPIN I1, encoding the plasminogen activator (PA) inhibitor neuroserpin (NS), is commonly expressed in the brain. The PA could degrade the thrombus through activating the fibrinolytic enzyme, and take part in other neuro‐matrix reactions at the same time 127. Under normal circumstances, neurons will overexpress NS to resist the adverse reactions that derived from over secretion of plasma enzymes.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%